2016
DOI: 10.1039/c6cc02063a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic transformation of esters of 1,2-azido alcohols into α-amido ketones

Abstract: The esters of 1,2-azido alcohols were transformed into α-amido ketones without external oxidants through the Ru-catalyzed formation of N-H imines with the liberation of N2 followed by intramolecular migration of the acyl moiety. A wide range of α-amido ketones were obtained, and one-pot transformation into the corresponding oxazoles (or a thiazole) was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…They observed that the Cp^ ligand endows interesting catalytic activities to the ruthenium complex. , Arenes are produced from the reaction of alkynes (Scheme a), while hydrobenzamides are formed in the reaction of benzyl azide (Scheme b) . The catalytic activity of 1 for the transformation of benzyl azide attracted our attention, because N–H benzaldimine was proposed as the key intermediate. , In fact, we found that its catalytic activity is not only limited to the reaction with benzyl azides but also effective for that with alkyl azides to generate the corresponding N–H imines . Various N -acetyl enamides can be synthesized by the catalytic transformation of alkyl azides in the presence of acetic anhydride (Scheme c)…”
Section: Introductionmentioning
confidence: 98%
“…They observed that the Cp^ ligand endows interesting catalytic activities to the ruthenium complex. , Arenes are produced from the reaction of alkynes (Scheme a), while hydrobenzamides are formed in the reaction of benzyl azide (Scheme b) . The catalytic activity of 1 for the transformation of benzyl azide attracted our attention, because N–H benzaldimine was proposed as the key intermediate. , In fact, we found that its catalytic activity is not only limited to the reaction with benzyl azides but also effective for that with alkyl azides to generate the corresponding N–H imines . Various N -acetyl enamides can be synthesized by the catalytic transformation of alkyl azides in the presence of acetic anhydride (Scheme c)…”
Section: Introductionmentioning
confidence: 98%
“…55 In 2016, Park and Rhee demonstrated that the α-hydroxy imine intermediate present in a Heyns rearrangement could be also formed from 1,2-azidoacetates by ruthenium catalysis. 56 The authors reported an improved yield for 1,2-azidoacetates, and this approach was subsequently applied to the synthesis of a wide range of α-amido ketones, forming the products in 53-94% yield.…”
Section: Rickmentioning
confidence: 99%
“…The α-amido ketones are very important structural motifs that are widely found in pharmaceuticals and several natural active molecules, such as herbicides, fungicides, and enzyme inhibitors. They are also important synthetic intermediates, for instance in the synthesis of N -heterocycles such as oxazoles, imidazoles, thiazoles, and others. Therefore, considerable efforts have been devoted to their synthesis. Nevertheless, some of these synthetic methods suffer from the following drawbacks: the difficulties of preparing starting substrates, rigorous conditions, and/or limitations of the substrate scope. Therefore, new synthetic methods featuring high atomic efficiency and operational simplicity are still under great demand.…”
Section: Introductionmentioning
confidence: 99%